Answer:
and
![a_(n)=a_(n-1)+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/puhtl3ge5nv0u1mfl33db798e1kw6duy1i.png)
Explanation:
The sequence is given by
.
Now, putting n = 1,
.
Now, putting n = 2,
![a_(2)=-4+4(2)=4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tl5eera3b0bej1w7ijt8gbbxs4myjy22if.png)
Therefore,
.........(1)
Again, putting n = 3,
![a_(3)=-4+4(3) =8](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ixey7q4fbtpc47zd7ocsmsd0okrd8ckgd8.png)
Therefore,
.......... (2)
Hence, from equations (1) and (2), we can write
and
![a_(n)=a_(n-1)+4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/puhtl3ge5nv0u1mfl33db798e1kw6duy1i.png)
So, this above relation gives the recursive rule for the given sequence. (Answer)